1983
DOI: 10.1063/1.93937
|View full text |Cite
|
Sign up to set email alerts
|

Switchable coaxial optical coupler using a liquid crystal mixture

Abstract: A novel coaxial form of optical coupler has been constructed in which 95% intensity modulation was achieved, using a liquid crystal mixture as the electro-optic medium. The behavior of this coupler with varying temperature and applied voltage has been elucidated by comparison with the behavior of the same coupler when the liquid crystal was replaced by a silicone oil whose refractive index could be reproducibly and controllably varied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In most studies liquid crystals are used as cladding. Examples include liquid-crystal-clad tapered fibers [I], liquid-crystaloverlay side-polished fiber [2]-[4], directional couplers with liquid crystal sandwiched between two side polished fibers [5], and coaxial fiber couplers embedded in liquid crystal [6]. These studies have demonstrated the feasibility of using optical fibers clad with liquid crystal to build switches, modulators, polarizers, and couplers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies liquid crystals are used as cladding. Examples include liquid-crystal-clad tapered fibers [I], liquid-crystaloverlay side-polished fiber [2]-[4], directional couplers with liquid crystal sandwiched between two side polished fibers [5], and coaxial fiber couplers embedded in liquid crystal [6]. These studies have demonstrated the feasibility of using optical fibers clad with liquid crystal to build switches, modulators, polarizers, and couplers.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some studies in which liquid crystals are used as the fiber core [7]- [IO]. Among those experimental studies that have used liquid crystals as the fiber cladding [1]- [6], none have made liquid crystals with a radial molecular director configuration. It has been proposed [ 1 I ] that by using liquid crystals with a radial configuration as the fiber cladding, one may be able to fabricate polarization-sensitive fiber devices.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of the use of LCFs has been in the fabrication of directional couplers, optical switches, modulators, sensors etc. [9][10][11][12][13][14]. In most of the applications, conventional optical fibers are cladded with liquid crystals.…”
Section: Introductionmentioning
confidence: 99%